Situation Report: Romania, 5 May 1977 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Individual Farmers Hold Conference National Conference of Romanian Writers Again Postponed Bucharest and Provincial Writers' Associations Elect New Officers New Regulations on Visas for Travel Abroad by Romanians Prime Minister Manescu Visits Czechoslovakia Egyptian Vice-President in Bucharest Ceausescu to Visit Australia, Possible Other Western Pacific States